2018
DOI: 10.9734/jamb/2018/39955
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Profile and Molecular Characterization of Extended-spectrum Beta-lactamase Genes in Enterobacteria Isolated from Human, Animal and Environment

Abstract: Objective: The aim of this study is to determine the antibiotic resistance profile and characterize extended spectrum beta-lactamase gene of enterobacteria strains isolated from human biological products, fecal matter of animals and the environment. Materials and Methods: Enterobacteria producing ESBL strains were isolated from human products, fecal matter of healthy animals (cattle, sheep and pigs) intended for human consumption and environment (hospital effluents and municipal sewage) using homemade medium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Other studies have found that blaNDM is the primary CR-KP gene found in neonatal patients [17], whereas blaKPC has been found in adults and older children [23]. Our findings also confirmed blaNDM as the prevailing carbapenemase gene within CR-KP isolates, aligning with prior research [17,24], and other reports from China [25]. Additionally, we identified two CR-KP strains expressing the blaKPC gene found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have found that blaNDM is the primary CR-KP gene found in neonatal patients [17], whereas blaKPC has been found in adults and older children [23]. Our findings also confirmed blaNDM as the prevailing carbapenemase gene within CR-KP isolates, aligning with prior research [17,24], and other reports from China [25]. Additionally, we identified two CR-KP strains expressing the blaKPC gene found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, our results show a prevalence of identified MDR isolates belonging to the genera Salmonella spp. (Carole et al 2018). In addition, recent work has shown the presence of these species in raw greywater discharged to the environment without treatment in Israel (Porob et al 2020) and Yemen (Noman et al 2022).…”
Section: Biochemical Characteristics Of Mdr Bacterial Strainsmentioning
confidence: 97%
“…An analysis of 83 studies conducted in Africa showed a prevalence of carbapenemase-producing bacteria isolated in hospitals ranging from 3% to 67.7%, with a mortality rate of up to 67% [ 36 ]. Beta-lactamases-producing bacteria and quinolone-resistant bacteria have been detected in humans, but also animals, and the environment [ 37 , 38 ]. Up to 35% of isolates from animals and 93.2% from humans have shown resistance to quinolones [ 37 ].…”
Section: Global Antimicrobial Resistance and The Need For Novel Compoundsmentioning
confidence: 99%